2022
DOI: 10.3390/su142013113
|View full text |Cite
|
Sign up to set email alerts
|

Narrative Insights Reveal the Motivations of Young Agricultural Entrepreneurs in Laos

Abstract: The participation of youth in agricultural entrepreneurship (agripreneurship) is beneficial for the sustainable development of agrarian societies that are transitioning towards the commercialization of agriculture. Accordingly, we investigated the phenomena that motivate practicing young, small- and medium-scale agripreneurs to pursue their careers, using the Lao People’s Democratic Republic (Laos) as a case study. To achieve this, we applied narrative inquiry techniques to the accounts of 74 young Laotian agr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 47 publications
2
3
0
Order By: Relevance
“…As a result, the study's findings confirm that social awareness is critical to improving the commercialization of smallholder farming in general, and oyster mushroom production in particular. The findings of the study also agree with those of [ 53 ], who identified income benefit as the most important motivator for young agricultural entrepreneurs. Farmers frequently view income as a means of achieving personal independence, financially supporting children/and or parents, financing schooling, acquiring study materials and/or machinery (e.g., vehicles) for themselves or others, extending their existing resources and time in activities to escape poverty, and/or developing their agricultural livelihoods through labour reduction and efficiency improvements [ 53 ].…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…As a result, the study's findings confirm that social awareness is critical to improving the commercialization of smallholder farming in general, and oyster mushroom production in particular. The findings of the study also agree with those of [ 53 ], who identified income benefit as the most important motivator for young agricultural entrepreneurs. Farmers frequently view income as a means of achieving personal independence, financially supporting children/and or parents, financing schooling, acquiring study materials and/or machinery (e.g., vehicles) for themselves or others, extending their existing resources and time in activities to escape poverty, and/or developing their agricultural livelihoods through labour reduction and efficiency improvements [ 53 ].…”
Section: Resultssupporting
confidence: 90%
“…The findings of the study also agree with those of [ 53 ], who identified income benefit as the most important motivator for young agricultural entrepreneurs. Farmers frequently view income as a means of achieving personal independence, financially supporting children/and or parents, financing schooling, acquiring study materials and/or machinery (e.g., vehicles) for themselves or others, extending their existing resources and time in activities to escape poverty, and/or developing their agricultural livelihoods through labour reduction and efficiency improvements [ 53 ]. Thus, mushroom farmers commercialize oyster mushrooms because they believe it is highly profitable and provide a steady source of income.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations